2008
DOI: 10.1177/1533317507312622
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Goal-Oriented Rehabilitation Program in Mild Cognitive Impairment: A Pilot Study

Abstract: As this goal-oriented rehabilitation program in MCI resulted in some improvements in cognition, occupational performance, and QoL, further randomized controlled studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 24 publications
(27 reference statements)
7
53
0
4
Order By: Relevance
“…Given the relative lack of tests and growing importance of such measures, it is clear that the development of ecologically valid tests would benefit rehabilitation research as well as the general field of Neuropsychology. 5,7,15,16,17,18,24,25,27,30,31,33 12 Narrative memory (other) 3,23,28,30 18,23,26,33, 15,21,22,30,31,33 6 Rivermead Behavioural Memory Test (RBMT) 7,8,16,17,26,27,31,33,34 3,7,23,30,31,36 1,3,4,5,15,28,29,32 1 The ...…”
Section: Methodological Challenge 4: Outcome Measuresmentioning
confidence: 99%
“…Given the relative lack of tests and growing importance of such measures, it is clear that the development of ecologically valid tests would benefit rehabilitation research as well as the general field of Neuropsychology. 5,7,15,16,17,18,24,25,27,30,31,33 12 Narrative memory (other) 3,23,28,30 18,23,26,33, 15,21,22,30,31,33 6 Rivermead Behavioural Memory Test (RBMT) 7,8,16,17,26,27,31,33,34 3,7,23,30,31,36 1,3,4,5,15,28,29,32 1 The ...…”
Section: Methodological Challenge 4: Outcome Measuresmentioning
confidence: 99%
“…The results of our study might be limited by the relatively small sample size (n = 25) although other cognitive intervention studies recruited even fewer participants (n < 20, e.g., [12,14]). When using a bootstrapping technique [46] to evaluate the stability of our key finding, the same variables became significant in 72% (volume of the left entorhinal cortex) and 85% (motivation) of all 1000 subsamples (Supplementary Table 5).…”
Section: Limitationmentioning
confidence: 93%
“…The combined training study by Londos and colleagues [12] for example, found 47% improved, 40% remained unchanged, while 13% worsened in processing speed. In another study in individuals with subjective, but not objective, memory impairment (SMI, a population at increased risk of developing dementia; n = 19), 21% worsened after cognitive training [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Goal-oriented rehabilitation with an educational component, memory strategies, mind-mapping and goal planning, led to better occupational performance and quality of life (Londos et al 2008). …”
Section: Introductionmentioning
confidence: 99%